As dificuldades da escolarização do deficiente visual no ensino regular-escola estadual modelo de araguaíana tocantins. - BARRETO, Genilse Alves Vieira (Universidade Federal do Tocantins, 2023)
The present study aims to reflect the schooling of the visually impaired in steady education, considering that the inclusion of students with disabilities in the regular school is a topic of discursions in the educational environment, so it is of fundamental importance that the school as a whole be prepared Appropriately to receive these students, with the objective of helping them in the effective learning process. The visually impaired students need a quality education and professionals prepared to attend them with adapted resources, which can favor means of access of knowledge, respecting and valuing the needs of each one. This work was carried out in a pioneering school in specialized educational service of students with visual impairment, located in the city of Araguaína, being divided in two parts, initially bibliographical research and then field research, in order to compare or associate the theory with The practice, in order to contribute to a better understanding of the topic in question. The school has several resources and has the work done by a teacher who is able to attend the student, who makes use of the available material. Interviews were carried out with visually impaired students, support teacher and teacher of mathematics in the common room, and it was noticed that there is still discrimination between common students and students with disabilities, as well as the resources available in the school are sub-used by teachers regular. The inclusion of the visually impaired student in regular education is not only about placing him in a common class, it is up to the school, preparing to train professionals in the goal of perceiving diversity and differentiating each student in their schooling process.